Analysis of the Effect of Workload and Organizational Culture on Competency-Mediated Auditor Performance - Desinta Ardiana Wulandari; Muryati (Journal of Management Research and Studies, 2024)
This research aims to determine the analysis of the influence of workload and organizational culture on auditor performance mediated by competency. Research was conducted on auditors of the Probolinggo Regional Inspectorate. The population in this research as a whole is all auditors in the Probolinggo regional Inspectorate, totaling 55 people. The entire population in this study was sampled. Data analysis in order to test the hypothesis in this research uses a multivariate Structural Equation Models (SEM) model with a Partial Least Square (PLS) approach. The application used to process this data is SmartPLS version 3.2.9. Based on the results of the data analysis that has been carried out, it can be concluded as follows: Workload has a negative effect on auditor performance, meaning that a low workload can encourage increased auditor performance. Organizational culture has a positive effect on auditor performance, meaning that organizational culture is able to encourage increased auditor performance. Competency can encourage improvements in auditor performance. Workload is able to indirectly encourage an increase in auditor performance mediated by competency. Likewise, organizational culture is able to indirectly encourage improvements in auditor performance. The results of this analysis are strengthened by the results of the accepted hypothesis for the four variables.